1996
DOI: 10.1182/blood.v88.5.1576.1576
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin can promote erythroid progenitor survival by repressing apoptosis through Bcl-XL and Bcl-2

Abstract: Erythropoietin (Epo), the hormone that is the principal regulator of red blood cell production, interacts with high-affinity receptors on the surface of erythroid progenitor cells and maintains their survival. Epo has been shown to promote cell viability by repressing apoptosis; however, the molecular mechanism involved is unclear. In the present studies we have examined whether Epo acts as a survival factor through the regulation of the bcl-2 family of apoptosis-regulatory genes. We addressed this issue in HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
9

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(97 citation statements)
references
References 27 publications
1
87
0
9
Order By: Relevance
“…They reported that blocking the activity of TNF-α with a specific chimeric human/mouse monoclonal antibody improves the ACD seen in patients with RA and the beneficial effect of the treatment is mediated by down-regulating the TNF-α-induced apoptotic mechanisms in bone marrow (45). However, deprivation of Epo induces apoptosis of immature erythroid colony-forming cells through down-regulation of the Bcl-X (L) anti-apoptotic protein (46). Thus ACD is not only caused by increased TNF-α but also by IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that blocking the activity of TNF-α with a specific chimeric human/mouse monoclonal antibody improves the ACD seen in patients with RA and the beneficial effect of the treatment is mediated by down-regulating the TNF-α-induced apoptotic mechanisms in bone marrow (45). However, deprivation of Epo induces apoptosis of immature erythroid colony-forming cells through down-regulation of the Bcl-X (L) anti-apoptotic protein (46). Thus ACD is not only caused by increased TNF-α but also by IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the antiapoptotic effect of Epo both in hematopoiesis and neurons. Silva et al (59) studied a human erythroid progenitor cell line and showed that apoptosis was repressed by Epo via up-regulation of the Bcl-X L gene, an antiapoptotic gene of the Bcl-2 family. This concept is supported by the finding that Bcl-X L knockout mice exhibit severe anemia during embryogenesis (60).…”
Section: Inflammation and Apoptosismentioning
confidence: 99%
“…In addition to activating a program of erythroid gene expression (Welch et al, 2004), GATA-1 serves an antiapoptotic function by regulating the expression of Bcl-x L in erythroid cells, and cooperates with EPO signalling pathways to promote erythroid cell survival (Silva et al, 1999;Gregoli and Boundurant, 1997;Gregory et al, 1999). Furthermore, EPOdependent activation of the factor STAT5 is also involved in the induction of Bcl-x L expression (Silva et al, 1999;Socolovsky et al, 1999).…”
Section: Introductionmentioning
confidence: 99%